Stopping Speed in the Stop-Change Task: Experimental Design Matters! - Gordi, Vera Michaela; Drueke, Barbara; Gauggel, Siegfried; Antons, Stephanie; Loevenich, Rebecca; Mols, Paul; Boecker, Maren (Frontiers in Psychology, 2019)
Previous research comparing the speed of inhibiting a motor response in no-foreknowledge vs. foreknowledge conditions revealed inconsistent findings. While some studies found stopping to be faster in the no-foreknowledge condition, others reported that it was faster in the foreknowledge condition. One possible explanation for the heterogeneous results might be differences in experimental design between those studies. Given this, we wanted to scrutinize whether it makes any difference if foreknowledge and no-foreknowledge are investigated in a context in which both conditions are presented separated from each other (block design) vs. in a context in which both conditions occur intermingled (event-related design). To address this question a modified stop-change task was used. In Experiment 1 no-foreknowledge and foreknowledge trials were imbedded in a block design, while Experiment 2 made use of an event-related design. We found that inhibition speed as measured with the stop signal reaction time (SSRT) was faster in the foreknowledge as compared to the no-foreknowledge condition of the event-related study, whereas no differences in SSRT between both conditions were revealed in the block design study. Analyses of reaction times to the go stimulus reflect that participants tended to slow down their go responses in both experimental contexts. However, in the foreknowledge condition of the event-related study, this strategic slowing was especially pronounced, a finding we refer to as “strategic delay effect” (SDE), and significantly correlated with SSRT. In sum our results suggest that inhibition speed is susceptible to strategic bias resulting from differences in experimental setup.